PERLINDUNGAN HUKUM WISATAWAN DALAM PENGEMBANGAN WISATA HALAL DI NUSA TENGGARA BARAT: Legal Protection of Tourists in the Development of Halal Tourism in West Nusa Tenggara - Listyaningrum, Novita; Philona, Rinda; Andrianto, Sis Nanda Kus; Awaludin, Awaludin (Ganec Swara, 2025)
Halal tourism is growing along with the increasing need of Muslim tourists for destinations that comply with Syariah values. This study explores the legal protection of tourists in the development of halal tourism in West Nusa Tenggara (NTB) based on Regional Regulation Number 2 of 2016. Using the normative method, secondary data in regulations and related literature are analyzed to assess the implementation of tourist protection. The study results indicate that NTB has great potential as a halal destination, but implementing legal protection for the comfort and safety of tourists still needs strengthening. In conclusion, the development of halal tourism must be accompanied by clearer regulations and effective supervision to guarantee the rights of tourists, especially comfort and safety. Collaboration between the government, business actors, and the community is needed so that halal tourism can grow sustainably while increasing the competitiveness of NTB as a leading destination.